Top-down versus bottom-up macroeconomics - Paul De Grauwe (Center for Economic Studies and ifo Institute (CESifo), 2010)
I distinguish two types of macroeconomic models. The first type are top-down models in which some or all agents are capable of understanding the whole picture and use this superior information to determine their optimal plans. The second type are bottom-up models in which all agents experience cognitive limitations. As a result, these agents are only capable of understanding and using small bits of information. These are models in which agents use simple rules of behavior. These models are not devoid of rationality. Agents in these models behave rationally in that they are willing to learn from their mistakes. These two types of models produce a radically different macroeconomic dynamics. I analyze these differences.
Keywords: E10; E32; D83; 330; DSGE-model; imperfect information; heuristics; animal spirits; Makroökonomik; Dynamisches Gleichgewicht; Sunspot; Unvollkommene Information; Mikroökonomische Fundierung; Theorie